2003
DOI: 10.1051/forest:2003034
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between soil factors, Quercus robur health, Collybia fusipes root infection and Phytophthora presence

Abstract: -About sixty oaks (Quercus robur), with different status of crown health, located in three plots in north eastern France were assessed for their degree of infection by C. fusipes. Baiting of Phytophthora spp. from soil was carried out at different seasons in a sub sample of these oaks. The variability of soil characteristics, such as depth to waterlogging signs and depth to a gravel layer limiting rooting was evaluated. Soil factors were tightly correlated. Infection induced by C. fusipes was significantly mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 22 publications
4
17
0
Order By: Relevance
“…These results agree with a previous study which showed that, at the plot scale, the severity of root damages induced by C. fusipes on Q. robur increased with an increase in soil sand content but decreased with the degree of waterlogging (Camy et al 2003a). Furthermore, our results are in agreement with those of different field surveys concerning Relative risk of decline associated with infection Fig.…”
Section: Discussionsupporting
confidence: 93%
“…These results agree with a previous study which showed that, at the plot scale, the severity of root damages induced by C. fusipes on Q. robur increased with an increase in soil sand content but decreased with the degree of waterlogging (Camy et al 2003a). Furthermore, our results are in agreement with those of different field surveys concerning Relative risk of decline associated with infection Fig.…”
Section: Discussionsupporting
confidence: 93%
“…A lowering pH of the mineral soil is associated with reduction in fine-root growth and mycorrhizal development, higher nitrogen/cation ratios, and aluminium (Al) toxicity, and as a result, increased sensitivity of the root systems to environmental stress (Demchik and Sharpe 2000;Göttlein et al 1999). Low soil pH has been shown to benefit oak root pathogens (Camy et al 2003) and can, therefore, provide an indirect link between crown condition and secondary stress factors. However, the opposite may also hold true.…”
Section: Soil Ph and Tree Agementioning
confidence: 99%
“…Agrilus spp. have been linked to root infections by Collybia fusipes and presence of Phytophthora in Q. robur [4] and have been suspected of transmitting pathogenic fungi from infected to healthy trees, which raised questions about their secondary role [20,30].…”
Section: Introductionmentioning
confidence: 99%